Editorial Vol13 no2 - Laura Steckley (Scottish Journal of Residential Child Care)
Welcome to the September 2014 issue of the Scottish Journal of Residential Child Care. It's a pivotal time here in Scotland with the Scottish Independence Referendum fast approaching. On 18 September, Scotland will decide whether to remain in the United Kingdom or to become an independent nation. There has been a flurry of discussion and debate, the like of which I’ve not seen during my 15 years in this country.